Reoperasi dan Non Reoperasi Penyakit Hirschsprung Dikaitkan dengan Profil Klinikopatologik Ujung Proksimal Reseksi di Departemen Patologi Anatomik FKUI/RSCM Tahun 2015 sampai 2019 - Permata Warastridewi, Arie; Krisnuhoni, Ening (Perhimpunan Dokter Spesialis Patologi Anatomik Indonesia (PDSPA), 2023)
Background Hirschsprung’s disease (HD) is a developmental disorder of the enteric nervous system, which is characterized by the absence of ganglion cells in the submucosal and myenteric plexuses. The success of surgery is influenced by many factors, one of which is the presence of histopathological abnormalities in the proximal part of the HD rectosigmoid resection. The aim of this study is to determine whether there are any histological characteristics associated with Hirschsprung's disease that would necessitate reoperation at the Department of Anatomical Pathology Faculty of Medicine Universitas Indonesia/Dr. Cipto Mangunkusumo Hospital (FMUI/CMH). Methods This was an analytical study using a cross-sectional design and secondary data from the Department of Anatomical Pathology Faculty of Medicine Universitas Indonesia/Dr. Cipto Mangunkusumo Hospital (FMUI/CMH) archives between 2015 and 2019. At the proximal end, histopathological examinations were performed to determine mature ganglion, nerve thickening, normal ganglion number, perineural inflammation, and serositis. The patient's age at the time of surgery, gender, the type of surgery, and the patient's age at the time of reoperation were all recorded. Results From the 64 resection cases, 15 reoperation resection cases and 49 non-reoperation resection cases were obtained. Of the 15 reoperation cases, the histopathological investigation revealed fifteen cases of mature ganglion, ten cases of nerve thickening, and fourteen cases of normal ganglion. There was no perineural inflammation in fifteen cases, and no serositis in fourteen cases. A p value of 0.026 was obtained for the patient's age at the time of the operation. Conclusion There are several factors that determine pasients with Hirschsprung disease who undergo reoperation after resection. The age of the patient at the time of resection is one of the factors that can affect the occurence of reoperation in patients with Hirschsprung disease.